Malaysia, Sarawak formulating digital strategies - Ahmad Azaini, bin manaf; Tan, Georgette (BorneoPost Online, 2017)
KUCHING: Malaysia and Sarawak are aggressively formulating their digital strategies that attempt to develop and strengthen the application of arts and its relation to the community.